Bioethics between Imaginary and Reality: Tracing Science Fiction and Its Shaping of Transplant Medicine Protocols in Japan. Issue 1 (1st March 2019) - Sasaki, Kaori
Abstract: By extending the late Osamu Kanamori's notion of science fiction (sci-fi) as it "re-articulate[s] various issues that bioethical studies had formally discussed, " this paper provides a cultural analysis of Japanese sci-fi stories from the 1990s with reference to the exchange of body parts. By focusing on the time when organ transplantation from brain-dead donors was part of many intensive debates, this paper pays particular attention to the fictional representations of humanity, which feature body-part exchanges between the living and the dead, in genres ranging from Noh 能 dramas to manga 漫画. In this paper I shed light on two issues: (1) how sci-fi representations described the matter of humanity vis-à-vis exchanging parts of the body, and (2) in what ways and on what terms bioethical discourses relating to Japanese organ transplant medicine from brain-dead donors were rearticulated through these sci-fi narratives. I also argue that such rearticulated values were inscribed in the process of constructing the bioethical code of practice in transplant medicine and deathbed care that took place during the late 1990s. By doing so, this paper confirms the role that sci-fi plays in bioethical imaginations, as Kanamori has pointed out and as can also be seen in East Asian societies like Japan.